Zgodnja zaznava nevrodegenerativnih bolezni - Povše, Lara (Placebo, 2024)
As the incidence of neurodegenerative diseases increases, so does the need for their early detection. Biological markers such as tau proteins, Aß42, PrP, ?-synuclein and neurofilament light chain offer promising possibilities for use in screening programs and simultaneously represent the future of early neurodegenerative disease diagnosis. Concurrently, innovative technologies and new analyses of existing methods are being developed, such as electroencephalography, which could complement existing diagnostic approaches.
Keywords: amiloid-ß; beljakovina tau; biološki označevalci; elektroencefalografija; Nevrodegenerativne bolezni